2011
DOI: 10.1007/s11894-011-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Management of Ulcerative Colitis

Abstract: The treatment options for inflammatory bowel disease have expanded with the introduction of biological therapies. Recently published controlled clinical trials were searched and those that impact the clinical management of ulcerative colitis (UC) are discussed in this review. In the management of mild to moderate UC, mesalamine still remains the first choice of drug. The newly developed once daily formulations have shown equal efficacy to divided doses and possibly portend better compliance owing to a simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 105 publications
0
9
0
2
Order By: Relevance
“…Interestingly, despite high prevalence being reported elsewhere (North America and Europe), no patients in our cohort tested positive for C. difficile . Regardless, it remains important to exclude bacterial pathogens in every episode of ASC as intensifying immmunosuppression in the face of colonic infection can lead to dire circumstances and increase the risk of colectomy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, despite high prevalence being reported elsewhere (North America and Europe), no patients in our cohort tested positive for C. difficile . Regardless, it remains important to exclude bacterial pathogens in every episode of ASC as intensifying immmunosuppression in the face of colonic infection can lead to dire circumstances and increase the risk of colectomy …”
Section: Discussionmentioning
confidence: 99%
“…14 Most (90%) of our cohort underwent colonic examination; however, CMV was excluded on biopsy in only 40% of admissions. Much evidence has surfaced implicating CMV infection in refractory ASC, 15 demonstrating CMV to be a risk factor for colectomy. [16][17][18][19] The importance of concurrent CMV infection was seen in one patient who initially improved but then rapidly declined, eventually coming to colectomy despite IV Aciclovir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, the mainstays of treatment have been systemic and topical corticosteroids and 5-aminosalicylates (5-ASA), and immunomodulators such as 6-mercaptopurine (6-MP), azathioprene, cyclosporine, and methotrexate. Although inexpensive and generally well tolerated, steroids are unsuitable for longterm use, 5-ASA are mostly useful only for mild-moderate disease, and 6-MP and azathioprene are incapable of inducing clinical remission, whereas cyclosporine, though useful in acute severe disease, is not suitable for chronic treatment [30]. Infliximab was the first biological inhibitor of TNF-a to be approved for treatment of IBD (reviewed in [31]).…”
Section: Inhibition Of Tnf-a In the Treatment Of Ibdmentioning
confidence: 99%
“…Corticosteroids have been the primary therapies in moderate to severe UC for years. Those who fail to respond to treatment with corticosteroids, or who present with severely active UC, should be considered as candidates for rescue treatment 1 . Our previous work revealed that anaemia, need for blood transfusion, and frequency of previous hospitalizations significantly determines the response to early parenteral corticosteroid therapy.…”
Section: Introductionmentioning
confidence: 99%